Respuesta :

Answer:

f(x) = 1/x

Step-by-step explanation:

h(x) = f(g(x)) = f(x-6) = 1/x-6

1/x-6 could only be accomplished if f(x) = 1/x

Assuming f(x) = 1/x and g(x) = x-6, f(g(x)) = f(x-6) = 1/x-6

Since f(g(x)) = 1/x-6 = h(x), we've proven that f(x) = 1/x.

The given functions are illustrations of a composite function, where the function f(x) is:

[tex]f(x) = \frac{1}{x}[/tex]

Given that:

[tex]h(x) = \frac{1}{x - 6}[/tex]

[tex]g(x) = x - 6[/tex]

f o g can be written as f(g(x))

So, we have:

[tex]h(x) = f(g(x))[/tex]

Rewrite as:

[tex]f(g(x)) = \frac{1 }{x - 6}[/tex]

Substitute g(x) for x - 6

[tex]f(g(x)) = \frac{1 }{g(x)}[/tex]

Replace g(x) with x

[tex]f(x) = \frac{1}{x}[/tex]

Hence, the function f(x) is: [tex]f(x) = \frac{1}{x}[/tex]

Read more about composite functions at:

https://brainly.com/question/8776301